The conflict in the story by A. P. Chekhov «In the ravine»: axiological aspect - Kalyutchik, Natalya F. (Journal of the Belarusian State University. Philology, 2022)
The conflict in the story by A. P. Chekhov «In the ravine» in its axiological aspect is examined as value polarisation within the fictional world of the literary work. Christian semantics of the conflict is explicated. In accordance with the principle of isomorphism (A. P. Chudakov) this conflict is found on such levels of the story as space, characters’ system, plot, inner world of the character. The novelty of the article is to reveal specific lyrical nature of the story’s conflict: in the Chekhovian individual conflict’s model poetics of open oppositions is subduded by the principle of antinomian motifs cumulation. So there is an incongruity between discourse boundaries of the conflict and the text in the story. Series of images and motifs, which are out of event line, build higher the conflict in empirical life. For the first time the inner world of the protagonist inactive in regard to the plot, not being on the side of either Lipa or Aksinya, the conflict parties, is examined as a semantic focus of the conflict.
Keywords: Chekhov’s prose; conflict; axiology; binary opposition; isomorphism; motif; Easter nature